Optimizing Vehicle Routing and Scheduling under Time Constraints - Karlo Bala; Michele Bandecchi; Dejan Brcanov; Nebojša Gvozdenović (Anali Ekonomskog fakulteta u Subotici, 2024)
The Vehicle Routing Problem is essential in logistics for optimizing customer routes, especially in time-sensitive variants. This paper presents a two-stage algorithm for the Vehicle Routing Problem with Time Windows. It effectively minimizes the number of vehicles, with transportation costs resulting just 0,38% above the best solution found on Solomon test instances. The approach limits search time to about 10 minutes, effectively balancing complexity and solution quality.